2010
DOI: 10.1038/sj.bjc.6605538
|View full text |Cite
|
Sign up to set email alerts
|

The role of MMP-9 in the anti-angiogenic effect of secreted protein acidic and rich in cysteine

Abstract: BACKGROUND: Secreted protein acidic and rich in cysteine (SPARC), a matricellular glycoprotein, modulates cellular interaction with the extracellular matrix and is capable of altering the growth of various cancers. We therefore sought to determine the effect of SPARC expression on medulloblastoma tumour growth and angiogenesis. METHODS: To this extent, we selected three SPARC full-length cDNA overexpressed clones (Daoy-SP). Consequences of SPARC overexpression were studied in terms of cell growth, angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 53 publications
4
53
0
2
Order By: Relevance
“…Our results showed that our chalcones also inhibited angiogenesis according to the chick embryo CAM model, suggesting the potential antiangiogenic effect of these structures, as previously shown with the 2-hydroxy-4-methoxy chalcone via the blockade of the vascular endothelial growth factor receptor signal pathway (26,38). The effect of the chalcones on MMP-9 could also be responsible for this inhibition of angiogenesis (39).…”
Section: Discussionsupporting
confidence: 84%
“…Our results showed that our chalcones also inhibited angiogenesis according to the chick embryo CAM model, suggesting the potential antiangiogenic effect of these structures, as previously shown with the 2-hydroxy-4-methoxy chalcone via the blockade of the vascular endothelial growth factor receptor signal pathway (26,38). The effect of the chalcones on MMP-9 could also be responsible for this inhibition of angiogenesis (39).…”
Section: Discussionsupporting
confidence: 84%
“…58 In tumor cells, SPARC overexpression resulted in a decrease in pro-MMP-9. 59 Other groups have examined the effects of SPARC suppression. Tumors grown in SPARC-null mice exhibited reduced deposition of fibrillar collagen types I and III, basement membrane collagen IV, and the collagen-associated proteoglycan decorin.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation technique of the dorsal skin-fold chamber model has been described previously (34). Briefly, diffusion chambers with control-, Hand-1OE-, or FL-uPAR-transfected stable cells (2 Â 10 6 ) were placed subcutaneously in the skin through the superficial incision made horizontally along the edge of the dorsal air sac.…”
Section: Dorsal Skin-fold Chamber Modelmentioning
confidence: 99%